Approximate Estimation of Man-Day in Ship Block Production: A Two-Stage Stochastic Program - Genc, Yusuf; Kafali, Mustafa; Celebi, Ugur Bugra (SCIENDO, 2024)
It is critical to estimate the workforce requirements for the production of blocks in shipbuilding. In this study, the number of workforce (man-day) required for the production of a passenger ship's double bottom block was estimated. Initially, the production of the block was observed, and the average working performance of the mounting, welding, and grinding workers was recorded. Block drawings were examined and the work required was calculated. The amount of work increased, depending on any revisions required due to incorrect or incomplete designs. The average working performance of an employee is uncertain due to environmental factors, including the weather and working conditions, as well as health (both physical and mental). A two-stage stochastic programming model with recourse was established to estimate man-day required and a Sample Average Approximation (SAA) technique was used to obtain a near-optimum solution. The results of the study were compared with shipyard records and an agreement of approximately 90% was achieved.
Keywords: Shipbuilding; Block Production; Planning; Stochastic Modelling; PERFORMANCE EVALUATION; PRODUCTION LINE; MANAGEMENT; SIMULATION; DESIGN; SYSTEM; MODEL; Engineering